Хобби гадкого утенка: роман / Д. А. Донцова - Донцова Дарья (Иронический детектив, 2002)
Экземпляры: ф.6 (2003) / Инвентарный номер: 44867 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44